Synthesis and graphitization of phenolic resins for carbon-containing refractory applications - Talabi, Segun Isaac (2020)
Carbon-containing refractories’ (CCRs) present special chemical and thermomechanical properties, which depend on the presence of carbonaceous phase with a structure similar to those of graphite. However, phenolic resins that are commonly used as binder for such refractories produce amorphous carbon, which can limit their performance. Consequently, this research focused on the synthesis and graphitization of these resins under temperatures and conditions suitable for refractory production. In the study, some series of experiments were conducted to investigate the role of boron oxide, boric acid and ferrocene as graphitizing agent for phenolic resins under various processing conditions such as mixing technique and heating procedure. Both conventional (commercial and laboratory synthesized products) and lignin modified phenolic resins were considered. The resulting carbon samples were characterized using X-ray Diffractometer (XRD) to determine the amount of generated graphitic carbon after carbonization. Transmission Electron Microscope (TEM) and Scanning Electron Microscope (SEM) were also used to corroborate the information obtained from the XRD analysis. The results showed that these additives can induce crystalline carbons generation during pyrolysis depending on the resin chemistry and processing parameters. The mechanism leading to carbon crystallization was attributed to the formation of B‒O‒C bonds for the boron compounds modified resins. The B‒O‒C bonds has a lower binding energy (compared to C‒C), which permits the rotation/reorganization that is necessary for graphitic carbons production. Similarly, Fe3C acted as active sites for crystalline carbon generation during pyrolysis of the resins-ferrocene formulations. Thermogravimetric analysis (TGA) of the carbon samples show that several factors such as bond strength, composition and atoms arrangement control their oxidation resistance. Moreover, the prepared CCR castables show improved oxidation resistance based on in-situ graphitization of the binder component.